Implementasi Pembelajaran Kitab Ta’zimul Ilmi dalam Meningkatkan Minat Belajar Mahasantri Ma’had Aly Jajar Surakarta - Ridha, Achmad Rasyid; Winarno, Andhika Sarfatra; Ghafur, Okta Abdul; Ardianto, Risko Aris; Slamet, Slamet (TSAQOFAH, 2024)
The blessing of knowledge begins with the interest of a student. The greater the interest, the greater the attention to the manners of seeking knowledge. The Ta'zimul Ilmi book is a book that discusses 20 manners in seeking knowledge and is accompanied by examples of the interests, enthusiasm, and manners of previous scholars. Learning the Ta'zimul Ilmi book at Ma'had Aly Jajar Surakarta is the Ma'had's way of increasing the interest of its students in learning. This study aims to determine the extent to which the implementation of learning the Ta'zimul Ilmi book has increased the interest of students in learning. The research method used is a descriptive qualitative research approach. This study was located at Ma'had Aly Jajar Surakarta. The main data sources were the principal, teachers, and students. Data collection was carried out by means of observation, interviews, and documentation. The researcher used triangulation to check the validity of the data. The research data collected were then analyzed using data analysis techniques, namely, data reduction techniques, data presentation, and drawing conclusions. After being observed and researched, it was found that learning with the book could boost the interest of students in learning. In fact, this learning can provide students with a deep understanding of the importance of seeking knowledge and the manners in achieving it.